Fistulous-type vein of Galen malformation phantom model for endovascular training and research. (10th August 2016) - Meila, Dan; Melber, Katharina; Grieb, Dominik; Jacobs, Collin; Lanfermann, Heinrich; Brassel, Friedhelm
Abstract : Introduction: Vein of Galen malformation (VGM), a high-flow intracranial arteriovenous shunt, is among the most severe neurovascular diseases in childhood. In many cases untreated children die or survive only severely disabled. Endovascular embolization is the preferred treatment. Objective: To develop a simple fistulous-type VGM phantom model for teaching and training of different endovascular treatment methods and to investigate new treatment options and devices. Methods: An experimental in vitro pulsatile phantom model was developed imitating a high-flow fistulous-type VGM, which is typical, especially in the neonatal phase. Pressure measurements at different arterial sites were performed before and after closure of the VGM. Closure of the VGM was achieved by coiling using a combined microcatheter-based transvenous and transarterial approach called 'kissing microcatheter technique'. Results: The behaviour of the phantom model in vitro under fluoroscopy and under angiographic runs was extremely similar to that in in vivo conditions in children. The results showed that intra-arterial pressures changed and increased statistically significantly at all measurement sites after embolization, as in human arteriovenous malformation. We also demonstrated different and complementary visualizations of hemodynamics and angioarchitecture by antegrade and retrograde microcatheter injections. Conclusions: Our phantom model behaves like a typical fistulous-type VGM and can be used in vitro for teaching and training and for further research. It offers a new and better understanding of hemodynamics and angioarchitecture in the endovascular management of VGM.